HUBUNGAN SUPERVISI AKADEMIK KEPALA SEKOLAH DENGAN KEPUASAN KERJA GURU SMP NEGERI 22 MEDAN - Hendri Fauza; Makmur Syukri; Faujiah Hanum Pane (Jurnal Sabilarrasyad, 2021)
This study aims to determine the relationship between the Principal's Academic Supervision with Teacher Job Satisfaction at SMP Negeri 22 Medan. This research is a descriptive quantitative research with a survey method approach. The subjects or samples of the study were 30 teachers at SMP Negeri 22 Medan. Sampling using total sampling technique. The data collection technique uses a questionnaire and Pearson Product Moment correlation analysis, because to find out a relationship between two variables, namely the Principal Academic Supervision variable (X) and the Teacher Job Satisfaction variable (Y). The results of this study indicate that (1) based on the tendency test of the Principal's Academic Supervision (X) is classified as high or good with a score of 30%. (2) the results of the tendency test for Teacher Job Satisfaction (Y) are classified as high with a value of 37%. (3) there is a positive and significant relationship between the Principal's Academic Supervision and Teacher Job Satisfaction at SMP Negeri 22 Medan, by comparing the value of rcount = 0.655, which is greater than the value of rtable = 0.361 with N=30 at a significance level of 5% or = 0.05. The correlation between the principal's academic supervision and teacher job satisfaction 0.655 is in the high category, therefore Ha is accepted and Ho is rejected.